PENGARUH FASILITAS PERPAJAKAN, KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - Meiliyani; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to obtain empirical evidence about the effect of taxation facilities, return on assets, leverage, firm size, fixed asset ownership intensity, number of commissioners, commissioners and directors' compensation, and institutional ownership to tax management with the effective tax rate as a measurement indicator. The research objects are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from year 2019 to 2021. The number of companies that meet all the research sampling criteria using the purposive sampling method is 73 companies with a total of 219 data. The hypothesis test used to determine the effect of each independent variable on tax management is a multiple regression model. The results showed that commissioners and directors' compensation had an effect on tax management, and seven other variables, such as tax facilities, return on assets, leverage, firm size, intensity of fixed asset ownership, number of commissioners and institutional ownership had no effect on tax management.